DEVELOPMENT OF EDUCATIONAL AND PEDAGOGICAL FORECASTING IN THE UKRAINIAN SOCIALIST SOVIET REPUBLIC DURING THE WORLD WAR II AND THE POST-WAR PERIOD (1940 – 1960) - Serhii Cherniak (International Journal of Innovative Technologies in Social Science, 2026)
The article highlights the development of the problem of educational and pedagogical forecasting in the Ukrainian Soviet Socialist Republic during the World War ІІ and in the post-war period (1940 – 1960). The scientist identifies conditional periods regarding the development of Soviet schooling in Ukraine during the war years. The teacher monitors changes in the demographic situation in the country. The researcher pays special attention during the specified period to improving the work of pedagogical education institutions. The scientist describes socio-political changes in domestic educational legislation. The researcher argues that the main thing in the restructuring of the public education system after the war was to combine learning with productive work.